Effect of Tanijau Organic Fertilizer and SMS Agrobost Organic Fertilizer on the Growth and Production of Green Eggplant (Solanummelongena L) F1 RatihHijau Hybrid - Eko Nur Budiyarto; Abdul Patah, Helda Syahfari (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
The purpose of this research is to know the effect of Tanijau organic fertilizer and organic fertilizer SMS Agrobost and its interaction with green eggplant growth and yield.The research method using Completely Randomized Design (RAL) in a 4x4 factorial experiment, with two treatment factors, was repeated as many as 4 repetitions. Factor I is the dose of Tanijau organic fertilizer (t), consisting of 4 levels, that is: without organic fertilizer Tanijau or control (t0), 2kg / polybag (t1), 4kg / polybag (t2), and 6kg / polybag (t3) . Factor II is the concentration of organic fertilizer SMS Agrobost (a), consisting of 4 levels, namely: without organic fertilizer SMS Agrobost or control (a0), 5ml / liter water (a1), 10ml / liter water (a2), and 15ml / liter of water (a3).The results showed that Tanijau organic fertilizer (t) was very different on plant height 15 days after planting, 30 days after planting, 45 days after flowering age, harvest age, weight per fruit, fruit weight per plant and the amount of fruit per plant is most achieved in the treatment of organic fertilizer Tanijau 6kg / polybag (t3) is1.519.56gr, while the least fruit cultivation is achieved at the treatment of t0 (without the dosage of Tanijau organic fertilizer) that is1.082,93gr.The effect of organic fertilizer SMS Agrobost differed significantly on plant height of planting age, flowering age, harvest age, number of fruits per plant, average weight per fruit, fruit weight per plant, fruit length per plant and fruit diameter per plant and number of fruit per plant. Treatment interaction was significantly different to fruit weight per plant, but was not significantly different from plant height 15, 30 and 45 days after planting.